The Implementation of the Think Pair Share Learning Model to Improve Understanding of Exponents - Imroatul Ma'rufah; Moh. Syadidul Itqan; Ayustika Raudatul Jannah (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
Mathematics learning, especially on the topic of exponents, is a fundamental component that supports students’ logical thinking and problem-solving skills. However, in practice, this topic often poses significant difficulties for eighth grade students of MTsN 1 Probolinggo. These difficulties are indicated by low learning outcomes and students’ limited ability to apply exponent concepts correctly. One of the main contributing factors is the low level of active student involvement during the learning process, where learning activities tend to be teacher-centered and provide limited opportunities for students to think, discuss, and collaborate. If this condition is not addressed, it may hinder students’ conceptual understanding and negatively impact subsequent mathematics learning. Therefore, it is necessary to implement an innovative learning model that can actively engage students and improve their conceptual understanding. This study aims to improve the understanding of the concept of exponents through the application of the Think Pair Share (TPS) cooperative learning model using the Classroom Action Research (CAR) method. The study was conducted in two cycles with 15 students as subjects. The research instruments consisted of a concept understanding test and student activity observation sheets. The results showed a significant increase in the average score and student learning completeness, from an average score of 50 in the pre-cycle to 90 in the second cycle, while the percentage of learning completeness increased from 46.7% to 100%. In addition, discussion and collaboration activities among students also improved, indicating more optimal student involvement during the learning process. These findings indicate that the Think Pair Share learning model is effective in improving the understanding of the concept of exponents among eighth grade students of MTsN 1 Probolinggo